PROSES PENGELOLAAN UNTUK KEBERHASILAN KBK - ., Sarbiran (Jurnal Cakrawala Pendidikan, 2004)
The Competency-Based Curriculum (CBC) is not only a philoso phy but also a methodology, which assists schools or other educational institutions to improve the quality ofstudents' behavior and competen cies. As the methodology deals with curriculum implementation, the teachers should have some alternative techniques ofprocessing class management suitable forteaching and learning activities. Some ofthe techniques are benchmarldng; brainstonning; cause and effect diagrams; "bows and whys" diagrams; forcefield analyses; measurement graphs; Pareto analyses; problem solving techniques; readiness and capability graphs; and statistical methods. Those techniques are not to give the teacher a notion ofworking harder but a notion ofworking smarter. The techniques are deceptively simple but provide a clarity and struc ture incollaborative working and a focus on core pmposes; all enhance working relationships as well as reducing the waste oftime usually ex perienced inmeetings. All ofthese require practice and review inorder to work effectively. Multiple C's are needed for supporting the compe tency: Commitment, Consistency, Conscientiousness, and Confidence. Also educationa11eadership ofevery teacher is absolutely necessary. Withoutthose, CBC will not fully be a success. Key words: curriculum, competencies, process